ICREGA’14 - Renewable Energy: Generation and Applications - Hamdan, Mohammad O.; Hejase, Hassan A.N.; Noura, Hassan M.; Fardoun, Abbas A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book collects the edited and reviewed contributions presented in the 3rd International Conference on Renewable Energy: Generation and Applications” ICREGA’14, organized by the UAE University in Al-Ain. This conference aims to disseminate knowledge on methods, policies and technologies related to renewable energy and it acknowledges the leadership of the UAE which committed to a 7% renewable energy target by 2020. The demands and developments in renewable energy generation and applications are rapidly growing and are facing many challenges at different levels such as basic science, engineering system design, energy policy and sustainable development. This edition presents new contributions related to recent renewable energy case studies, developments in biofuel, energy storage, solar and wind energy, integrated systems and sustainable power production. In the spirit of the ICREGA’14, the volume has been produced after the conference so that the authors had the possibility to incorporate comments and discussions raised during the meeting. The contributions have been grouped under the following topics:          Efficient Energy Utilization          Electrical Energy Market, Management and Economics          Energy Storage Systems          Environmental Issues          Fuel Cells Systems          Green Buildings          Intelligent Energy/Power Transmission and Distribution          Solar Photovoltaic and Thermal Energy          Wind Energy Systems.
Preface -- Efficient Energy Utilization -- Electrical Energy Market, Management and Economics -- Energy Storage Systems -- Environmental Issues -- Fuel Cells Systems -- Green Buildings -- Intelligent Energy/Power Transmission and Distribution -- Solar Photovoltaic and Thermal Energy -- Wind Energy Systems.
Keywords: Renewable energy resources; Energy systems; Energy efficiency; Renewable and Green Energy; Renewable and Green Energy; Energy Systems; Energy Efficiency